THE USE OF SHOW AND TELL METHOD TO IMPROVE STUDENTS SPEAKING ABILITY - Rahayu, Arum (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2023)
This study examines the application of the Show and Tell learning method on the